Hospitality internship program insights - Arif Kamisan Pusiran; Yuzainy Janin; Sarimah Ismail; Lorna Jimi Dalinting (Internship program insights, 2020)
Purpose The purpose of this paper is to provide some insights on current industry internship practices and the perceptions of students during their internship experience. This paper also highlights some issues pertaining to internship from the students’ and the industry’s perspective Design/methodology/approach The paper utilises qualitative research methodology using in-depth interviews.. Findings The sources of conflict arising between the two parties need to be addressed carefully so as to create a win–win situation. The paper offers some suggestions for higher education institutions as to how to establish better guidelines for student internships as well as for industry operators.. Originality/value Internship, industrial training, practical training or work-integrated learning refers to the involvement of students, institutions and colleges of higher learning in the industry. Internship provides an opportunity for students to experience first-hand, a work-related learning process. Given this, the involvement of industry in accepting students onto well-designed internship programmes is very much needed, so as to ensure the completion of a balanced period of study for a career in hospitality and tourism.